A new species of the genus Hypogastrura from coastal wetlands of East China (Collembola: Hypogastruridae) - Jiang, Jigang; Tang, Boping; Chen, Jian-Xiu (Zootaxa, 2007)
A new species, Hypogastrura sheyangensis, from East China is described. It belongs to H. manubrialis group of species within the genus and is easily separated from the other members of the group by a combination of characters, foot structure, furca, antennal sensilla, thoracic and abdominal chaetotaxy. A comparison is made between the new species, other species of Hypogastrura known from China and three other similar species in the genus.